Analysis and Modelling of Intelligent Gate Valve with Fault Detection and Prevention System for Fabrication Using 3D Printing Method - Mohamad Zakir, B. (Springer Science and Business Media Deutschland GmbH, 2022)
Gate valves are one of the most extremely used valves in the oil and gas industry. However, previous researchers have found that gate valve tends to fail before its appointed time without prior notice. The causes of failures are often due to many factors which includes internal passing through gate even in fully closed position, wear, and external leakage at packing area. The goal of this study is to design a gate valve with reduced risk of failures and added intelligent functionality which will subsequently lengthen the lifespan of the valve and prevent unnoticed early failures. According to a previous computational study done in 2-dimension (2D), a gate valveâs wedge angle is best around 8Â° at which the fluid inside the valve generates the lowest velocity and pressure and hence the lowest gate deformation. To verify the claim, a 3-dimensional (3D) Computational Fluid Dynamic (CFD) and Finite Element Analysis (FEA) method is conducted to study the fluid flow characteristics and deformation within gate valves in real-world scenario. From the CFD and FEA, the effect of varying wedge gate angle to the velocity, pressure, and gate deformation is studied and areas within gate valve that are most susceptible to failures are identified. Following the analysis, the valve geometry is improved to achieve optimum working conditions and lower risk of failures. In addition to the computational analysis, a study is also made to identify the type of sensor and the practicability of sensor embedded in metal body to add for the intelligent functionality of the valve, so that it is capable of early fault detection. In order to validate the CFD result obtained, a research paper that conducted the 2D analysis is referred to, and the analysis presented is performed identically in 2D via Altair SimLab. The percentage error is between 1 to 5. Results show that the 3D analysis contradicts previous 2D research that indicated an 8Âº wedge angle to be the best angle. According to the 3D analysis, the more inclined the wedge angle, the lower the pressure, velocity, and gate deformation, implying that an angle of 9Â° is better than 8Â° and an angle of 10Â° is better than 9Âº, hence the contradiction. The 3D result is more reliable and accurate as it is more practical in industry. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.